Islamic equity unit trust funds: macroeconomic determinants of NAV of Islamic equity unit trust funds: a case of Malaysia - Othman, Anwar Hasan Abdullah (LAP LAMBERT Academic Publishing, 2011)
The purpose of this study is to examine the relationship between the NAV of the Islamic equity unit trust funds and selected macroeconomic variables as well as the effect of the recent global financial crisis in the Malaysian financial industry. The study also compares the performance of Islamic and conventional unit trust funds for Malaysian capital market. This study facilitates the investors in making effective investment decisions by estimating the future direction of NAV of the Islamic equity unit trust fund using the expected trend in the macroeconomic variables. In addition, the empirical result of this study also presents the investors with new perspective of selecting the type of funds in their portfolio selection, whether Islamic equity fund or conventional equity fund.